Gomphonema Ehrenberg (Gomphonemataceae, Bacillariophyceae) in preserved environments from south Brazil and a proposal of a new species - Ferreira, Paula C.; Kava, Vanessa M.; Ludwig, Thelma A. V. (Phytotaxa, 2026)
A taxonomic study of the genus Gomphonema was conducted in periphytic samples collected in preserved environments of a mountainous region from southern Brazil, “Mananciais da Serra”, located in Piraquara, State of Paraná. The analyses were performed using light and scanning electron microscopy, resulting in the record of eight species of the genus Gomphonema. One of them, Gomphonema serrana P.C. Ferreira et T.V. Ludwig sp. nov., was formally proposed. The new species is proposed based on particular morphological characteristics summarized in the clavate-lanceolate valves whose margins gradually attenuate towards the acute apical and rounded basal poles. The basal margins are slightly concave. Also, a coarse granulation and an isolated central pore decorate the axial area. Gomphonema brasiliensis var. demerarae and G. reimeri are taxa similar to G. serrana and are properly compared. Gomphonema pseudobohemicum was recorded for the first time in Brazil, expanding knowledge of the global distribution of the genus. Furthermore, the results reinforce the role of diatoms as environmental bioindicators, as these species occur in low conductivity and acidic conditions, typical of well-preserved oligotrophic environments.